Direction of future research in EWOM: issues of credibility, format and impact - Ahmed Khan, Shamim; Hussin, Siti Rahayu; Abdul Hamid, Abu Bakar (2018)
Electronic word of mouth (eWOM) is an important tool for getting necessary useful information about a product or service. Although the concept of eWOM has attained substantial attention from the researchers, there are certain avenues of eWOM which have not been investigated thoroughly. The goal of this study is to highlight some of such avenues of eWOM where future researchers can focus on. For this purpose, three issues of eWOM were selected which are credibility of eWOM, format of eWOM and impact of eWOM. In recent years, credibility has become one of the most important issues regarding eWOM considering the widespread practice of counterfeit or fake online opinions. Format of eWOM is another important area because studies related to eWOM mostly focused on text-based eWOM. However, eWOM can be shared in different forms like text-based, video-based, mixture of text and visual etc. Very few studies have been undertaken to look into these diverse formats of eWOM. Impact of eWOM on different outcomes is the most extensively researched topic in eWOM literature. Despite this fact, impact of eWOM on some of the marketing related outcomes have received minimum attention from researchers as well as produced contradictory findings. Discussions about all three selected aspects of eWOM in this study shows the current state of literature as well as highlight the relevant literature gaps. Finally, some prospective research areas related to eWOM are presented which can be utilized by future researchers.